P.092 Health inequity and time from stroke onset to arrival trends: a single-centre experience. (June 2022) - Pai, AM; Nichol, D; MacGregor, D; Bhathal, I; Moharir, M; To, T; Ertl-Wagner, B; Kassner, A; deVeber, GA; Dlamini, N
Abstract : Background: Clinical outcomes following childhood arterial ischaemic stroke (AIS) depend on age at the time of stroke, infarct size and location. However, other important variables including health inequity and stroke onset to arrival times remain inadequately addressed. This study reported trends in health inequity and stroke onset to arrival times along with proximity to a stroke centre in Canada. Methods: Childhood AIS patients (N=234) with stroke onset between 2004-2019 at a Level 2 (comprehensive) stroke centre were included. Measures of material deprivation included household income, education, single-parent families, and housing quality. Patients were stratified into 3 cohorts (by date of stroke onset) and postal codes were categorized as minimal, moderate, or most deprived neighbourhoods. Results: Over the 16-year period, an increasing number of patients arrived from the most deprived neighbourhoods. Although, there was no significant association between material deprivation and stroke onset to arrival time, an increasing number of patients presented within 6 hours of stroke onset (χ 2 = 13.8, p = 0.008). Furthermore, most patients arrived from urban neighbourhoods. Conclusions: The faster stroke onset to arrival trend is encouraging, however, material deprivation trends are concerning. Thus, future studies exploring post-stroke outcomes should consider material deprivation, stroke onset to arrival times, and geographical proximity.